The Role of the Foundation in Improving the Quality of Madrasah Tsanawiyah Qurrotul Aini Cileungsi Bogor Education - Iskandar; Setyawan, Aris (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2022)
The purpose of this research is to find out, namely: (a). The role of the foundation in improving the quality of education at Madrasah Tsanawiyah Qurrotul Aini Cileungsi Bogor. (b) Factors inhibiting the improvement of the quality of education in Madrasah (c) The foundation's efforts to improve the quality of Madrasah education. This research method uses a qualitative approach that emphasizes the depth of information. Collection techniques include: (a). Observation (b). Interview (c). Documentation study. The results have shown that the role of the foundation is not maximized, in terms of procuring facilities and infrastructure, financial management and improving human resources. Inhibiting factors in improving the quality of Madrasah education. Educational facilities and infrastructure are minimal, sources of financial financing for education are not sufficient, teacher motivation is lacking in enthusiasm. Supporting factors in improving the quality of education are the roles and efforts of the chairman of the foundation in providing educational facilities and infrastructure, a financial management system that is always being improved and improving the welfare of educators and education staff.